Adolescents' Subjective Appraisals: Relationships with Body Image and Dieting Attempts - Samuel Chng; A. Sadiq Sani (Shiraz University of Medical Sciences, 2017)
Background: Current concerns around obesity, physical inactivity, eating disorders and their associated health consequences sustains the need for understanding body image and disordered eating in adolescence. Objectives: The study explored how subjective appraisals of health, familial support, wellbeing and weight are associated with body image and dieting attempts in adolescents. Methods: The study analysed data from a population-representative UK adolescent sample of 3,684 adolescents (aged between 11 and 16) from Understanding Society. Gender-stratified hierarchical and logistic regressions modelled the relationships between the adolescents' subjective appraisals of self (health, familial support, wellbeing and weight) and their body image and dieting attempts respectively. Results: Subjective appraisal of being overweight was the strongest and most consistent predictor of poorer body image (Bs = 1.17 to 1.19, P < 0.01) and higher likelihood of dieting and weight loss attempts in both males (odds ratios = 9.36 to 9.76, P < 0.001) and females (odds ratio = 8.88 to 9.43, P < 0.001). Positive appraisals of health and wellbeing were associated with positive body image (Bs = 0.25 to 0.55, P < 0.001). However, positive appraisals of family support were associated with dieting attempts in males (B = 1.34, P < 0.05). Conclusions: These highlight the importance of incorporating education components addressing wellbeing and family support into current adolescent public health programmes looking to mitigate risks of developing unhealthy weight control behaviours.